Peers and sources of information and their implications for adolescent sexual behavior - Khairil Fauzan K. (INSPIRA: Indonesian Journal of Psychological Research, 2020)
Current study aims to analyze factors that influence adolescents sexual behavior. This study was was explanatory research with associative explanatory methods The participants of this study were 38 high school students that recruited using purposive sampling method. The results reveled that adolescents that were strongly exposed to information sources were 60.5% and weak ones were 39.5%. Furthermore, peer influence is felt as strong as 36.8% and the influence is felt as weak is 63.2%. there was significant effect of information resources on adolescents’ sexual behavior (p < 0.05) while there was no significant effect of peers (p > 0.05).